2021
DOI: 10.1177/20503121211047063
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of cervical cancer screening and associated factors among women attending maternal health services at Aira Hospital, West Wollega, Ethiopia

Abstract: Background: Cervical cancer is one of the major noncommunicable public health problems among women globally. About 500,000 women develop cervical cancer each year, with an estimated 85% or more occurring in developing countries, including Ethiopia. Objective: The main objective of the study was to assess the knowledge of cervical cancer screening and its associated factors among women attending maternal health services at Aira hospital, West Wollega, Ethiopia. Methods: An institutional-based cross-sectional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
5
7
0
Order By: Relevance
“…12 Similarly, level of education allows women to not only improves their perception about the disease but also enhances their awareness on the importance of undergoing cervical cancer screening and was found congruent with the research conducted in West, Wollega, Ethopia. 13 Also, women with more children were able to receive awareness about cervical cancer risk factors, prevention and early screening through health care workers during their antenatal and postnatal visits; these results aligned with the study carried out in rural India. 14 Furthermore, a study from Karachi, Pakistan 1 also supports our findings i.e.…”
Section: Socio-demographic Factors With Media Attributed To Cervical ...supporting
confidence: 76%
“…12 Similarly, level of education allows women to not only improves their perception about the disease but also enhances their awareness on the importance of undergoing cervical cancer screening and was found congruent with the research conducted in West, Wollega, Ethopia. 13 Also, women with more children were able to receive awareness about cervical cancer risk factors, prevention and early screening through health care workers during their antenatal and postnatal visits; these results aligned with the study carried out in rural India. 14 Furthermore, a study from Karachi, Pakistan 1 also supports our findings i.e.…”
Section: Socio-demographic Factors With Media Attributed To Cervical ...supporting
confidence: 76%
“…Participation in CCS was extremely low, as less than 5% of the women studied had ever had in CCS. Similarly, women attending maternal and child health clinics in Ethiopia reported low knowledge of CCS [ 25 ]. The low level of public awareness about CCS and inadequate screening facilities in hospitals across Ghana could account for the observed finding.…”
Section: Discussionmentioning
confidence: 99%
“…Existing research from the SSA has identified various factors linked to the uptake of CCS. These factors encompass age [ 7 , 8 ], marital status [ 9 ], educational level [ 10 ], employment status [ 11 ], HIV status [ 12 ], smoking [ 13 ], alcohol consumption, exercise, susceptibility, and awareness of screening programs [ 14 ]. Moreover, there is an emerging interest in investigating the correlation between body mass index (BMI) and CCS in low- and middle-income settings.…”
Section: Introductionmentioning
confidence: 99%